Quests : design, theory, and history in games and narratives - Howard, Jeff, 1978- (Boca Raton : CRC Press, Taylor & Francis Group, 2022)
"Combining theory and practice, this updated new edition provides a complete overview of how to create deep and meaningful quests for games. It uses the Unity game engine in conjunction with Fungus and other free plugins to provide an accessible entry into quest design"--
OCLC-licensed vendor bibliographic record.
Keywords: COMPUTERS / Computer Graphics / Game Programming & Design; Video games -- Authorship; Quests (Expeditions); Quests (Expeditions) in literature